İbn Hazm’ın umum–husus yaklaşımı - Karlı, Merve (My University, 2022)
Zâhirîlik düşüncesinin en önemli temsilcisi olan İbn Hazm aynı zamanda bu mezhebi sistemleştiren kişidir. Dinin Hz. Peygamber hayattayken tamamen düzenlenip artık değiştirilemez olduğunu düşünen İbn Hazm’a göre ortaya çıkacak her meselenin cevabı Kur'an veya sünnette açıkça mevcut olup mükellefin yorumuna ihtiyaç bulunmamaktadır. Ona düşen yalnızca her şeyin hükmü bulunan bu kaynaklarda verilen bilgileri açığa çıkarmaktır. Bunun için de en temel araç dildir. Lafızları dilde belli manaları karşılamak üzere vazedenin Allah Teâlâ olduğunu kabul eden İbn Hazm’a göre hakikate ancak nasları, dilde konuldukları bu manalara hamletmekle ulaşılabilir. Bir delile dayanmaksızın lafızların dildeki bu manalarına ilave yapmak kıyas iken manadan eksiltmek ise tahsis olup her ikisi de batıldır. Tahsis edildiğine dair bir delil bulunmayan âm nasların delâleti konusunda üç görüş bulunmaktadır: İlki, bu lafızla kastedilenin ne olduğu belirleninceye kadar beklenilmesi gerektiği (tevakkuf), ikincisi lafızların hususi bir anlam için vazedilmiş olup bunun dışında bir anlama delâlet ettiğini söylemek için bir delile ihtiyaç olduğudur. İbn Hazm’ın da içinde bulunduğu çoğunluğun görüşüne göre ise âm lafız tahsis edilmediği sürece bütün fertlerine delâlet eder. Usul alimlerinin büyük çoğunluğu bu görüşte olmakla birlikte âm lafzın fertlerine delâletinin katiliği, kati olmayan delille tahsisinin imkânı, naslar arasında teâruz meydana geldiğinde aralarının nasıl telif edileceği gibi konularda farklı görüşler vardır. Bu çalışmada öncelikle İbn Hazm’ın lafız taksimine yer verilmiş; ardından yukarıda umum-husus konusuyla bağlantılı olduğunu belirttiğimiz meseleler onun perspektifinden ortaya konulmuştur.

Ibn Hazm, the most important representative of Zahiri school, is also the person who systematized this school. According to Ibn Hazm, who thinks that religion is completely regulated while the Prophet was alive and cannot be changed after him, the answer to every issue that arises is clearly available in the Qur’an or the Sunnah of the Prophet, and there is no need for the interpretation of the competent believer. His only duty is to reveal the information provided in these sources, where the ruling for everything can be found. The most fundamental tool to realize this is language. According to Ibn Hazm, who accepts that it is Allah Who has created the words to refer to certain meanings in the language, the truth can only be attained by understanding the texts based on these meanings in the language. Adding to these meanings of the words in the language without any evidence means analogy, while reducing their meanings is specification (takhsis) in meaning, both of which are false. There are three views on the specification of the texts with general meaning, for which there is no evidence regarding that they have been specified: The first is that one should wait until it is determined what is meant by this wording (tawaqquf), and the second is to claim that the words have been established for a specific meaning and evidence is needed to claim that they refer to a meaning other than that very specific meaning. According to the majority’s view, which includes Ibn Hazm, ‘amm (general)’ words refers to all its units unless it is specified. Although the majority of the scholars of the methodology of Islamic jurisprudence are of this opinion, there are different views on issues such as the certainty of the reference of the general word to all of its units, the possibility of its specification with non-conclusive evidence, and how to reconcile when there is a conflict between the textual sources. In this study, first of all, Ibn Hazm’s classification of the types of words (lafz) is introduced; then, the issues that we mentioned above that are related to the issue of ‘amm and khass are examined from his perspective.
Keywords: ‘Amm-Khaṣ; ‘Umūm-Khūṣuṣ; Âm-Has; Bayan; Beyân; Fıkıh Usulü; Ibn Hazm; Islamic law; İbn Hazm; İslam hukuku; İslâm Hukuku; Lafız Bahisleri; Methodology of Islamic Jurisprudence; Tahsis Islamic Law; Takhṣiṣ; The Subjects Related to Lafz; Umum-Husus; Zâhirîlik; Zahirites